2007
DOI: 10.1118/1.2757002
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of the modulation transfer function on the blocking layer thickness in amorphous selenium x‐ray detectors

Abstract: Blocking layers are used to reduce leakage current in amorphous selenium detectors. The effect of the thickness of the blocking layer on the presampling modulation transfer function (MTF) and on dark current was experimentally determined in prototype single-line CCD-based amorphous selenium (a-Se) x-ray detectors. The sampling pitch of the detectors evaluated was 25 microm and the blocking layer thicknesses varied from 1 to 51 microm. The blocking layers resided on the signal collection electrodes which, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…An n-layer (d) produced from the same alloy (Se:0.5%As without Cl) by cold deposition in which T substrate = 25°C. An n-i structure (Ç) produced as a sister sample for one of the X-ray detectors described in [10]. Both layers are produced from Se:0.2%As without Cl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An n-layer (d) produced from the same alloy (Se:0.5%As without Cl) by cold deposition in which T substrate = 25°C. An n-i structure (Ç) produced as a sister sample for one of the X-ray detectors described in [10]. Both layers are produced from Se:0.2%As without Cl.…”
Section: Discussionmentioning
confidence: 99%
“…4. This particular detector structure was recently used in prototype detectors for high-resolution mammography based on the slot scanning imaging technique [10]. Both layers in the latter structure were produced from Se:0.5%As alloy.…”
Section: Dark Current Densities In Single and Double Layer A-se X-raymentioning
confidence: 99%
“…6 is a photograph of the complete detector along with X-ray images of a resolution phantom obtained with this detector. Modulation transfer functions, MTFs, obtained on our experimental X-ray detectors [13] show that the spatial frequency f 0.5 (f at which MTF = 0.5) is about 11-14 lp mm À1 when d 6 15 lm. It was found that f 0.5 falls as d becomes thicker.…”
Section: Resultsmentioning
confidence: 98%
“…Differently scaled X-ray images of a resolution bar phantom that show the a-Se CCD X-ray detector can resolve bar patterns with resolution better than 16 lp mm À1 . detectors for high-resolution mammography based on a CCD readout circuit [12]. The complete detector was fabricated using a CCD chip, with a pixel size 20 lm  20 lm, coated with an i-n double layer a-Se with a Pt negative electrode.…”
Section: Resultsmentioning
confidence: 99%
“…This process is called "cold deposition" since the substrate temperature is well below the glass transition temperature of a-Se. Whereas the n-like blocking layer is small compared to the sampling pitch, the reduction of the MTF due to this layer will be small [17]. The fabrication of the n-like layers was completed by annealing the devices at 51 °C for 1 hour in the vacuum chamber.…”
Section: Fabrication Processmentioning
confidence: 99%